(untitled) (Global Journal of Management and Business Research, 2020)
The study examines the empirical relationship between exchange rate interest rate and inflation in the context of Sub - Sahara African countries using panel data over 1980-2012 periods The estimated values of the pooled fixed and random effects models reveal identical results that interest rate and inflation maintain a monotonous relationship with the exchange rate though the relationship is insignificant for interest rote only in the random effect model based on 1 level of significance However